Conditional mutagenesis in Drosophila. - Choi, C.M.; Vilain, S.; Langen, M.; Van Kelst, S.; De Geest, N.; Yan, J.; Verstreken, P.; Hassan, B.A. (Science, 2009)
Most genes function at multiple stages of metazoan development, in dividing and nondividing cells. Generating mouse conditional knock-outs (cKO), where a gene can be eliminated in a temporally and spatially controlled manner, is a valuable technique because it allows study of gene function at any stage of life. In contrast and despite the development of many other powerful genetic tools, cKO has thus far been lacking in Drosophila. We combined several recent molecular and genetic technical advances in an approach termed integrase-mediated approach for gene knock-out (IMAGO). IMAGO allows the replacement of any genomic sequence, such as a gene, with another desired sequence, including cKO alleles that can be used to create positively marked mutant cells. IMAGO should also be applicable to other genetic model organisms.